Sex‐limited penetrance of lymphedema to females with CELSR1 haploinsufficiency: A second family. Issue 5 (23rd August 2019) - Erickson, Robert P.; Lai, Li‐Wen; Mustacich, Debbie J.; Bernas, Michael J.; Kuo, Phillip H.; Witte, Marlys H.
Abstract: A second multigeneration family with hereditary lymphedema (LE) secondary to a variant in the planar polarity gene, CELSR1, is described. Dominant inheritance of the variant was discovered using whole‐exome sequencing and confirmed by Sanger sequencing. In contrast to heterozygous males, all heterozygous females showed LE during physical examination albeit variable in severity and age of onset. Lymphscintigraphy in affected females showed previously undescribed lymphatic abnormalities consistent with lymphangiectasia, valve dysfunction, and thoracic duct reflux. Abstract : Sex‐linked lymphedema in CELSR1 haploinsufficiency.